Patterns in Agricultural Loans under the Agricultural Credit Guarantee Scheme in Nigeria - Isiorhovoja, R.A. (Mediterranean Journal of Social Sciences, 2013)
This paper assessed the performance of the Agricultural Credit Guarantee Scheme (ACGS) with the objectives of: (i)determining the trend in the annual total number and value of loans guaranteed, (ii) ascertaining the direction of loansguaranteed, and (iii) determining the risk of non-repayment level associated with loans guaranteed to farmers. Data wereobtained from the Central Bank of Nigeria (CBN, 2010a) for the 20 year period of 1991 to 2010 and were analyzed by the useof tables, graphs and descriptive statistics of minimum, maximum and mean and risk measurement. Parts of the findings werethat the yearly total number and value of loans guaranteed by the Scheme and the number and value fully repaid were on theincrease; the risk of non-repayment was also on the increase though it nosedived in 2010. Further, that about 0.2% of theestimated households population in Nigeria was reached in terms of loans and that the average unit loan value guaranteedranged from N3,729.78 to N155,661.17. Individual farmers received upward of 92% and 76%, respectively, of annual numberand value of loans guaranteed. It was recommended that the Scheme should review and incorporation the lessons learnedfrom 1991 to 1999 into a new policy and strategy formulation and operation that would engender another era of low risk of nonrepaymentof loans with increases in loan expansion.